Analysis of spontaneous labor progression of breech presentation at term. - Ines Benmessaoud; Margot Jamey; Barbara Monard; Jean-Patrick Metz; Aude Bourtembourg-Matras; Rajeev Ramanah; Didier Riethmuller; Abdellah Hedjoudje; Nicolas Mottet (PLoS ONE, 2022)
Background Cervical dilatation curves are widely used to describe normal and abnormal labor progression for cephalic presentation. Labor curves for breech presentations have never been described. Objectives The aims of this study were to examine the pattern of labor progression in women with a breech presentation and to determine whether the type of breech or parity can influence the speed of cervical dilatation. Study design We analyzed the labor data from 349 women with a term, singleton, and breech fetus after spontaneous onset of labor in 2010-2018. Cesarean deliveries were excluded. The patterns of labor progression were described by examining the relationship between the elapsed times from the full dilatation and cervical dilatation stages. Average labor curves were developed using repeated-measures analysis with 3rd degree polynomial modeling. The results were interpreted according to parity and the type of breech. Results The first stage of labor progression was divided into a latency phase from 0 to 5 cm of dilatation and an active phase from 5 to 10 cm. In the active phase, the median speed of cervical dilatation was 1.67 cm/h [1.25, 2.61] (2 cm/h for multipara and 1.54 cm/h for nullipara). The difference by parity was significant in the active phase (p< 0.05). The cervical dilatation rate from 3 cm to 10 cm did not significantly differ between the complete and frank breeches (1.56 cm/h vs 1.75 cm/h, p = 0.48). However, the median cervical dilatation rate from 8 cm to complete dilatation was faster for complete breeches (1.92 cm/h versus 1.33 cm/h, p = 0.045). Conclusion As with cephalic presentation, the first stage of labor progression for breech presentation can be divided into a latent and active phase. Labor progression should be interpreted with respect to parity, and women should be informed that the type of breech does not seem to influence the cervical dilatation rate when there is adequate management.